2011
DOI: 10.3233/jad-2011-110524
|View full text |Cite
|
Sign up to set email alerts
|

Statins: The Role in the Treatment and Prevention of Alzheimer's Neurodegeneration

Abstract: Alzheimer's disease (AD) is a progressive neurodegenerative disease commonly seen in the elderly and is characterized by progressive cognitive and physical decline. Current understanding of AD pathogenesis revolves around amyloid-β peptide (Aβ), a product of the sequential proteolytic cleavage of the transmembrane amyloid-β protein precursor (AβPP) by β- and γ-secretase, enzymes found predominantly in the cholesterol rich micro domains of the cell membrane. Several risk factors for AD are associated with chole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
30
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 112 publications
1
30
0
1
Order By: Relevance
“…One study indicated that the application of a cholesterol-reducing LXR agonist improved the quantity of presynaptic boutons [7], regulated neuroinflammation, and decreased Aβ accumulation [26]. The administration of statins has also been demonstrated to protect against AD [27, 28]. Neural membranes contain several classes of phosphoglycerides, which not only constitute their backbone but also provide them with a suitable environment.…”
Section: Discussionmentioning
confidence: 99%
“…One study indicated that the application of a cholesterol-reducing LXR agonist improved the quantity of presynaptic boutons [7], regulated neuroinflammation, and decreased Aβ accumulation [26]. The administration of statins has also been demonstrated to protect against AD [27, 28]. Neural membranes contain several classes of phosphoglycerides, which not only constitute their backbone but also provide them with a suitable environment.…”
Section: Discussionmentioning
confidence: 99%
“…1.5 MAC: orthopedic surgery plus 2 h exposure of 1.5 MAC sevoflurane, n = 6. celastrol reduced cell death and Ab production by increasing HSP-70 and Bcl-2 expression and reducing NFkB, COX-2, and GSK-3b expression and oxidative stress . Additionally, atorvastatin had therapeutic potential in a mouse model of postoperative cognitive dysfunction, evoking protection from hippocampal interleukin-1b, reducing hippocampal endothelial COX-2 and NF-kB activation, decreasing microglial reactivity, and enhancing the phosphorylation of GSK-3b Pac-Soo et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Atorvastatin and pitavastatin reduce the level of oxidative stress, as revealed by the presence of 4HNE and AGE, in AD mouse brains, and improve insulin signaling and LDLR/ApoE systems, as well as the serum adiponectin/leptin balance [163]. Statins, in addition to their antihypercholesterolemic, pleiotropic and antiinflammatory effects, are being investigated for a potential therapeutic role in AD, though clinical studies are contradictory [161,164]. In a group of AD patients recruited for pharmacoge nomic studies treated with a multifactorial therapy for 1 year [49], we evaluated the effects of Sardilipin (ESAR94010; LipoEsar ® ; 500 mg/day; nutraceuti (Figure 3).…”
Section: Cholesterol Dysregulationmentioning
confidence: 98%
“…Statins are neuroprotective in stroke, cerebral ischemia, AD, Parkinson's disease, multiple sclerosis, epilepsy and trau matic brain injury [160]. Statins are widely prescribed for their cholesterol lowering ability [161]. By competitive inhibition of HMGCoA reductase, statins reduce the production of cholesterol and isoprenoid intermediates, including geranylgeranyl and farnesyl pyrophosphate.…”
Section: Cholesterol Dysregulationmentioning
confidence: 99%